1997
DOI: 10.1097/00003643-199709000-00005
|View full text |Cite
|
Sign up to set email alerts
|

COVERS for anaesthetic machines: an audit and standard

Abstract: pre-use checklist) re-audit of 102 completed checklists showed 20 tests revealing faults on 59 occasions All the anaesthetic machines in one District General (range 1.0-11.6%), 16 (27%) day to day and 43 (73%) Hospital were tested for faults on three occasions for non-recurring. COVERS supported by scheduled both audit and re-audit using an extended checklist regular comprehensive checking delegated to another based on that devised by the Association of Antime and performer is recommended as the mandatory aest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…This may have been considered unnecessary in a machine check that is based on the use of an oxygen analyser. However, this study found faults in the oxygen analyser in 11.3% of machine checks and other studies found the oxygen analyser to be absent or faulty in 25.4% and 55% of machine checks [7, 8]. In the light of these results, failure to check the oxygen failure warning alarm is difficult to justify.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…This may have been considered unnecessary in a machine check that is based on the use of an oxygen analyser. However, this study found faults in the oxygen analyser in 11.3% of machine checks and other studies found the oxygen analyser to be absent or faulty in 25.4% and 55% of machine checks [7, 8]. In the light of these results, failure to check the oxygen failure warning alarm is difficult to justify.…”
Section: Discussioncontrasting
confidence: 58%
“…Even when the presence of a carbon dioxide cylinder is not counted as a fault, faults were found in 30.3% of the machine checks in this study and the majority of these were potentially serious. Other studies have found the occurrence of faults to be at least as frequent as this [7, 8].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…min −1 maintained as an attempt to meet the requirements for minimal oxygen consumption of the patient’ with ‘minimum oxygen flow incorporated into safe anaesthesia machines’[1]. This setting was promoted as the minimum for adults first by Ohmeda then Dräger and became, effectively, a standard though none was formally created [2], and we incorporated it into our departmental comprehensive machine check [3]. The latest edition of Ward's Anaesthetic Equipment [4] considering Anti‐hypoxia Devices includes details of minimum standing flow of 175–250 ml.min −1 for Ohmeda and basal flow of 200–300 ml.min −1 for M & IE.…”
mentioning
confidence: 99%